Air Density Change Along the Pipe Surface During Pneumatic Transport Of Cotton - Turgunov Dilmurod Umarali o’g’li (International Journal on Human-Computing Studies, 2023)
This article examines the laws governing the density distribution of cotton and air mixes inside pipes. In the turbulent motion of the cotton and air combination, the connection between the air density and the movement of the air pressure from the tube's opening to the ventilator was investigated.